Urban and rural differences in outcomes of head and neck cancer. (20th September 2017) - Kim, Jason D.; Firouzbakht, Aryan; Ruan, Jenny Y.; Kornelsen, Emily; Moghaddamjou, Ali; Javaheri, Khodadad R.; Olson, Robert A.; Cheung, Winson Y.
Abstract : Objectives/Hypothesis: To assess for potential urban and rural disparities in head and neck cancer (HNC) outcomes within a single‐payer healthcare system. Study Design: A large retrospective population‐based cohort analysis of consecutive HNC patients treated in British Columbia, Canada between 2001 and 2010 was conducted. Methods: All patients diagnosed with HNC from 2001 to 2010 and referred to any one of five British Columbia Cancer Agency centers for management were reviewed. Based on census data, patients were classified into: 1) rural, 2) small urban, 3) moderate urban, and 4) large urban areas. Kaplan‐Meier methods and Cox regression models were used to correlate site of residence with overall survival (OS), controlling for prognostic factors that included sociodemographic and other tumor and treatment‐related characteristics. Results: We identified 3, 036 patients; the median age was 64 years, 26% were women, and 32% had Eastern Cooperative Oncology Group (ECOG) 0 or 1. The majority resided in large urban areas (55%) followed by rural (22%), moderate urban (13%), and small urban (10%). In regression analyses, smoking (hazard ratio [HR]: 2.10, 95% confidence interval [CI]: 1.28‐3.45, P  < .001), ECOG 2 + (HR: 3.44, 95% CI: 2.26‐5.22, P  < .001), oral cavity (HR: 1.54, 95% CI: 1.03‐2.32, P  = .04) and hypopharyngeal tumors (HR: 2.31, 95% CI: 1.42‐3.77, P  = .00), and large tumor size (HR: 1.69, 95% CI: 1.08‐2.64, P  = .02) were correlated with inferior OS, but site of residence was not. When stratified by type of treatment, OS remained similar irrespective of urban or rural residence. Conclusions: Urban–rural differences in HNC survival outcomes were not observed. Level of Evidence: 2c. Laryngoscope, 128:852–858, 2018